Nanomaterial Characterisation of Diluted Platina and Alcohol Control Samples - Rajendran, E.S. (Homeopathy, 2023)
Background The healing effects of homeopathic ultra-high potencies (UHPs) have always been a puzzle for material science, though recent research papers have now characterised the nanomaterial nature of several such UHPs. This study aimed to analyse the material content of clinically used potencies of the homeopathic medicine Platina (platinum) compared with alcohol control samples.Methods Potencies of Platina were analysed under dynamic light scattering (DLS), high resolution transmission electron microscopy (HRTEM) with energy dispersive spectroscopy (EDS) and selected area electron diffraction (SAED) to identify the nanomaterial content. As control samples, both unsuccussed and potencies of alcohol were analysed by using DLS and HRTEM.Results Platina 30c to CM: Nanoparticles were identified under DLS (mean particle size varying from 1.3 nm in 30c to 6.5 nm in CM) and HRTEM (particle size varying from 3.31 to 12.7 nm in 30c to 1.94 to 8.54 nm in CM). EDS confirmed the presence of platinum in all the samples of Platina. SAED analysis of Platina 30c, 200c, 1M and 10M confirmed also the presence of platinum dioxide (PtO2). For control samples, DLS and the HRTEM analyses of pharmaceutical grade unsuccussed alcohol and potentized Alcohol (6c, 12c and 30c) did not show any particles.Conclusion Homeopathic potentization generated NPs of platinum in ultra-dilutions. NPs in potencies of Platina showed platinum in EDS and PtO2 in SAED. Importantly, control samples of alcohol did not show the presence of particles under DLS or HRTEM.
Keywords: nanoparticles; nanopharmacology; ultra-high potencies; Platina